Construction and validation of the teacher perception questionnaire on intellectual disability and learning - Alulima Alulima, Lydia Dolores (2022)
It is indispensable that professionals enrolled in the Education System provide information about Intellectual disability and Learning, this information should go further than the evidence found and teachers perceptions. It is also necessary to have access to the assessment instruments. The main goal of this research was to validate the questionary about Intellectual disability for students of Primary and Secondary Education. This research was done in Ecuador (South America) the participants were teachers and school authorities of different schools. The contents of this questionary were validated by experts and V-AIKEN score method as pilot test. In addition, Cronbach’s alpha measure was applied to measure the reliability of the questionary and finally the exploratory factor analysis of the results. The pilot questionary consisted of 15 items and was applied to 180 teachers and school authorities, the V-AIKEN method reveled 90% to 100% of reliability of the 15 items. The accuracy showed by Cronbach’s alpha measure was 0,960 in the same way, two components were determined in the variance corresponding to each fact. The first component constitutes 69% of variance and the second component the results gives 32 % of variance. Thus, the first component nominated Inclusion of students with Intellectual Disability integrates 8 items and the second called Learning Development involves 6 items, this generated an interaction of interface of 0,76 and 0.64. This revealed a moderated positive correlation of both components. In conclusion the Validating Search Processes is continuous. Therefore, this process demonstrated that the questionary is appropriated to learn about the teacher’s perception on intellectual disability and the learning process.